Development of a novel binderless diamond grinding wheel for machining IC chips for failure analysis - Venkatesh, V. C.; Izman, S. (Elsevier B.V., 2007)
The objective of this research is to machine the silicon die of an IC chip and the surrounding chip packaging. The silicon die had to be reduced from a thickness of 85 ?m to about 50 ?m by a machining technique such that not a single transistor of the 40 million under the die is destroyed and at the same the die presents a mirror finish for examination on a back emission infra red microscope. The chip packaging had to be machined such that the six layers of power conduits in the form of copper traces and the dielectric (insulator) between them could be studied at low magnification for discontinuity. Initially electroplated diamond grinding pins were used for the die that was successful but it left undesirable tracks behind that remained even after polishing. These pins were not ideal for the soft but tough chip packaging. A new binderless diamond grinding wheel was developed that had a width equal to that of the IC chip die and also that of the width of the chip packaging with considerable success. This new wheel was also used to machine plano silicon and optical glass lenses successfully